2018
DOI: 10.3390/su10103417
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Diversity and Socioeconomic Perspectives of the Urban (Food) Forest of Accra, Ghana

Abstract: Urban and peri-urban forestry has emerged as a complementary measure to contribute towards eliminating urban hunger and improved nutritional security. However, there is scanty knowledge about the composition, diversity, and socioeconomic contributions of urban food trees in African cities. This paper examines the diversity and composition of the urban forest and food trees of Accra and sheds light on perceptions of urbanites regarding food tree cultivation and availability in the city. Using a mixed methods ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 41 publications
8
30
4
3
Order By: Relevance
“…However, 36 introduced species not taken into account have been identified in urban flora. The richness and diversity of species in this study are superior to those of some African cities studied such as Niamey which has 112 woody species belonging to 88 genera with 37 families and Maradi with 111 woody species belonging to 37 genera , with 34 families (Moussa et al, 2019), 109 ornamental species recorded in Dakar (Dieng et al, 2019) and 176 species reported in Kumassi (Nero et al, 2018), 132 species distributed in 95 genera and 32 families in Ziguinchor (Charahabil et al, 2018), Brazzaville 43 species belonging to 33 genera and 20 families in the sites studied, plus 28 other species in relics of forests located around the city (N'Zala and Miankodila, 2002). Our results are and lower than the 297 species of trees in Lomé in Togo (Raoufou and Kokou, 2013).…”
Section: Floristic Diversitycontrasting
confidence: 52%
“…However, 36 introduced species not taken into account have been identified in urban flora. The richness and diversity of species in this study are superior to those of some African cities studied such as Niamey which has 112 woody species belonging to 88 genera with 37 families and Maradi with 111 woody species belonging to 37 genera , with 34 families (Moussa et al, 2019), 109 ornamental species recorded in Dakar (Dieng et al, 2019) and 176 species reported in Kumassi (Nero et al, 2018), 132 species distributed in 95 genera and 32 families in Ziguinchor (Charahabil et al, 2018), Brazzaville 43 species belonging to 33 genera and 20 families in the sites studied, plus 28 other species in relics of forests located around the city (N'Zala and Miankodila, 2002). Our results are and lower than the 297 species of trees in Lomé in Togo (Raoufou and Kokou, 2013).…”
Section: Floristic Diversitycontrasting
confidence: 52%
“…Urban forests, including trees that are not only in woodlands, but also on streets, along streams, and in parks, provide important ecosystem services for urban and peri-urban populations [6]. Trees in cities contribute to the stability of the urban ecosystem [7], provide food [8], and have aesthetic aspects that contribute to the generation of economic and social benefits [9]. Urban green spaces are also important for attraction of tourism in city destinations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, du point de vue des services d'approvisionnement, les usages alimentaire, médicinal et sous forme de bois énergie sont les mieux connus par les populations. Par exemple, l'utilisation des fruits comme aliment est très répandue et ancrée dans les habitudes quotidiennes aussi bien à Grand-Popo que dans d'autres villes côtières du Bénin et d'Afrique de l'Ouest (Nero et al, 2018). Parmi les espèces qui fournissent le plus de services d'approvisionnement figure Cocos nucifera, qui est aussi bien utilisée dans les alignements que dans les plantations familiales.…”
Section: Vers Une Considération Des Services éCosystémiques Fournis Punclassified